The Influence of Artificial Intelligence and Brand Experience on Brand Equity in the Social Security Program for Workers - Mariana, Rita; Kurniawati; Masnita, Yolanda (Jurnal Economic Resource, 2025)
This study examines the influence of Artificial Intelligence (AI) and Brand Experience on the Brand Equity of BPJS Ketenagakerjaan. Against the backdrop of the importance of social protection in Indonesia's economic development, this study highlights how the application of AI, particularly through chatbots, can enhance service efficiency and user experience. The research method employs Structural Equation Modeling (SEM) to analyze data from 319 respondents. The results indicate that AI has a significant positive impact on Self Congruity and Consumer Empowerment, which ultimately enhance Brand Experience. Additionally, Brand Experience is proven to increase Brand Equity. These findings provide insights for BPJS Ketenagakerjaan in designing more effective and relevant service strategies in the digital age.